KEMAMPUAN REPRESENTASI MATEMATIS DAN KEMAMPUAN PEMBUKTIAN MATEMATIKA - Syafri, Fatrima Santri (JURNAL e-DuMath, 2017)
In mathematics, there are some mathematical ability to be possessed by learners and educators. Among them is a mathematical representation capability and the ability of mathematical proofs. Where the ability of the mathematical representation is a mathematical abilities with the disclosure of mathematical ideas (problems, statements, definitions, etc.) in various ways. In mathematics, a proof is a series of logical arguments that explain the truth of a statement. While the method of proof is developed aiming to improve the ability to understand the evidence, and do (proving) a mathematical statement.